Resistance, Reinhabitation, and Regime Change - David Gruenewald (Journal of Research in Rural Education, 2006)
Reciting poetry at a mathematics research symposium is a form of resistance, similar to Whitman's response to the astronomy lecture, which is to rise and glide and wander off. He was a New Yorker, raised in Brooklyn, wrote for and edited several newspapers, went to the opera weekly. Whitman was an experiencer; he sought the thing itself"direct experience"rather than its second-hand representation. I think we can therefore interpret anyone's walking out of this or any lecture as an act or resistance worthy of careful study.